EVALUASI HASIL BELAJAR TEMATIK DALAM PEMBELAJARAN DARING DI MI NURULLAH KEPUH CIREBON - Muflihatun Niswah; Aninditya Sri Nugraheni (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2020)
Thematic learning creates many opportunities that make students more participating and involved in learning activities. Therefore, many schools are trying to implement thematic learning in schools, including at Madrasah Ibtidaiyyah (MI) Nurulllah Kepuh Cirebon which is the main object of this research. However, the focus of this research is how to implement it in MI Nurullah Kepuh Cirebon. Thus, this study aims to determine how the implementation of thematic learning at MI Nurullah Kepuh Cirebon, including its effectiveness in improving the quality of learning, the obstacles experienced, and student learning outcomes from this thematic learning. By conducting research using a quantitative approach, the results show that thematic learning conducted by MI Nurullah Kepuh Cirebon is relatively effective. However, there are obstacles that are experienced, namely in the form of limited learning facilities, the media used in online learning, even the media used by the teacher. Student learning outcomes are quite good, and also increase student activity in the learning process. It can be said that the thematic learning carried out by MI Nurullah Kepuh Cirebon is relatively effective, but it still needs improvements in facilities to support thematic learning better. Keywords : Thematic